Selected Students’ Perspectives on International Service-Learning:A Case Study in Chajul, Guatemala - Caroline Black; Lori Moore; Gary Wingenbach; Tracy Rutherford (Journal of International Agricultural and Extension Education, 2013)
The purpose of this study wastoinvestigate a unique international service-learning experience between two non-governmental organizations (NGOs) and acollege of agriculture. This case studyfocused on a 25-day international service-learning study abroad program to Guatemalafor TexasA&M University students. Ashand Clayton’s (2009a) service-learningmodel was used for Texas A&M Universitystudents to complete service-learningprojects in the highlands of Guatemala. Thestudy abroad group, working with twoNGOs, completed multiple service-learningprojects in three rural communities. Nineundergraduate students documented theirexperiences through field logs and reflectionpapers. Five major themes were revealed instudents’ written artifacts: adaptation,culture, collaboration, communication, andvalue of knowledge. This internationalservice-learning opportunity empoweredstudents to embrace different cultures andlanguages while applying academicknowledge gained through study abroadcoursework in Guatemala. The results areuseful for informing the policies andpractices of future international service-learning opportunities through Texas A&MUniversity. Future research should expandour understanding of interaction betweenland-grant universities and NGOs tomaximize practical impacts of internationalservice-learning projects in college ofagriculture study abroad programs
Keywords: Service-Learning; Study Abroad; Higher Education; Culture; Communication; Diversity; Adaptation